A systematic review of longitudinal studies investigating the impact of cannabis use in patients with psychotic disorders. (3rd July 2021) - Athanassiou, Maria; Dumais, Alexandre; Gnanhoue, Gismonde; Abdel-Baki, Amal; Jutras-Aswad, Didier; Potvin, Stéphane
ABSTRACT: Introduction : Research has established a link between cannabis use and adverse psychotic outcomes in psychosis patients. However, we have yet to determine if this relationship is maintained when controlling for important confounding variables. The following systematic review aims to investigate if the association between cannabis use and psychotic outcomes is preserved when accounting for important confounders, and if discontinued use mitigates any potential negative impacts. Areas covered : The authors conducted an exhaustive search of the MEDLINE database and Google Scholar to identify articles pertaining to the systematic review. Thirty-three articles were retained for meeting the eligibility criteria. Expert opinion : The evidence confirms an overarching pattern of negative psychotic outcomes of cannabis intake in psychosis populations, even when accounting for crucial confounders. Psychosis patients should be informed with evidence-based health information regarding the effects of cannabis use. Clinicians should systematically evaluate cannabis intake patterns in psychosis patients and offer intervention services geared toward reducing problematic consumption. Researchers should record confounding factors in a more systematic manner in future longitudinal investigations while paying careful attention to the potency and dose–response effects of the ingested cannabis. Deciders will need to investigate the impact of cannabis regulations on psychosis populations.